Guidelines for the programmatic management of drug-resistant tuberculosis : emergency update 2008 (World Health Organization, 2008)
The emergence in 2006 of extensively drug-resistant strains of tuberculosis, especially in countries with a high prevalence of human immunodeficiency virus, is a serious threat to global public health and jeopardizes efforts to effectively control the disease. These important developments and the availability of new evidence related to the diagnosis and management of drug-resistant tuberculosis have mandated an urgent update of existing guidelines. Guidelines for the Programmatic Management of Drug-Resistant Tuberculosis: Emergency Updated Edition 2008 replaces previous publications by the World Health Organization on this subject. The Guidelines offer updated recommendations for the diagnosis and management of drug-resistant tuberculosis in a variety of geographical, economic and social settings, and the recording of data that enables the monitoring and evaluation of programs. Intended for use by both tuberculosis control programs and medical practitioners in low- and middle-income countries, the guidelines take into account a number of recommendations which will support the achievement by countries of the goals of the Global Plan to Stop TB 2006-2015 of the Stop TB Partnership.
Keywords: Antiretroviral Therapy, Highly Active; HIV Infections; HIV infekce; Antitubercular Agents; antituberkulotika; Tuberculosis, Multidrug-Resistant; vysoce aktivní antiretrovirová terapie; multirezistentní tuberkulóza; pneumologie a ftizeologie